BENTUK PENGGUNAAN LAHAN YANG TERKONVERSI AKIBAT PEMBANGUNAN JALAN TOL PADANG – SICINCIN DI KECAMATAN BATANG ANAI - RAHMI, ALFI (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This study aims to examine: 1) Analyzing the conditions of converted land use due to the construction of the Padang-Sicincin toll road. 2) Analyzing the area of ​​land use conversion and the type of land use converted due to the construction of the Padang-Sicincin toll road. This type of quantitative descriptive research with identification data processing techniques and accuracy test. The research results obtained include: (1) The land use conditions before and after the construction of the toll road show that the land use conditions before the construction of the toll road amounted to 15403.17 Ha, and after the construction of the toll road the land area changed to 15306.39 Ha. (2) The area of ​​land use conversion. The area of ​​converted land use in Batang Anai District is 96.78 Ha with a percentage of 0.63% with the type of converted land use, namely rice fields with an area of ​​52.84 Ha with a percentage of 54.60%. With the construction of the toll road, many people's lands have changed professions, such as rice and garden farmers to become laborers at PTs in Batang Anai District.